Reproductive biology - Prakash, Gayatri (Alpha Science International Ltd, 2007)
Reproductive biology provides a complete and an integrated approach to the study of essntials of mammalian reproduction including humans. It covers both introductory and fundamental aspects of developmental, anatomical, hormonal, physiological, biochemical and family welfare related knowledge of reproductive biology. The text in the book is well supported by tables and figures